Escalation Huddles: Facilitating Sepsis Activations Using Hospital-wide Escalation Processes. Issue 2 (March 2018) - Lockwood, Justin; Wathen, Beth; Rolison, Elise; Reese, Jennifer; Bajaj, Lalit; Swanson, Angela; Carpenter, Todd
Abstract : Background: Bedside huddles can be valuable parts of hospital sepsis responses. These huddles, however, risk duplication of effort with existing care escalation systems, and they may also be of value in settings other than sepsis. Streamlining care escalation processes may present an opportunity to improve sepsis responses. Objectives: To facilitate team-based discussion of patients with suspected sepsis as a step toward reducing time to first antibiotic administration. Methods: Existing care escalation frameworks were amended (Figs. 1, 2 ) and incorporated into rapid cycle process improvement initiatives on non-ICU units. New sepsis response resources were created to facilitate team communication, intravenous (IV) access, and timely antibiotic delivery (Fig. 3 ). Results: An Escalation Huddle system was created to bring local care teams together early during clinical deterioration, including cases of suspected sepsis. Rapid Response Team activation is available but not mandated. An Urgent IV & Blood Draw algorithm was created to facilitate IV access using a protocolized progression through existing hospital resources. An Inpatient Suspected Sepsis order set was created with antibiotic decision support and recommendations for evaluation of organ dysfunction. These processes have been improved through 3 "Plan, Do, Study, Act" cycles. Conclusions: Rather than create a separate sepsis response system, we chose to enhance existing hospital-wide escalation processes by formalizing an Escalation Huddle system and developing new tools to enhance sepsis responses within that system. We anticipate this approach will facilitate discussion of suspected sepsis cases and improve sepsis responses while avoiding inefficient or duplicative escalation actions by care team members.